2007
DOI: 10.1126/science.1139089
|View full text |Cite
|
Sign up to set email alerts
|

Control of Stress-Dependent Cardiac Growth and Gene Expression by a MicroRNA

Abstract: The heart responds to diverse forms of stress by hypertrophic growth accompanied by fibrosis and eventual diminution of contractility, which results from down-regulation of alpha-myosin heavy chain (alphaMHC) and up-regulation of betaMHC, the primary contractile proteins of the heart. We found that a cardiac-specific microRNA (miR-208) encoded by an intron of the alphaMHC gene is required for cardiomyocyte hypertrophy, fibrosis, and expression of betaMHC in response to stress and hypothyroidism. Thus, the alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

33
1,295
10
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,516 publications
(1,352 citation statements)
references
References 39 publications
33
1,295
10
14
Order By: Relevance
“…miR-489, which is highly expressed in quiescent SCs and is quickly downregulated during SC activation, helps to maintain the quiescent state of adult stem-cell populations by targeting Dek 27 . When miRNA expression in skeletal muscle is dysregulated, various skeletal muscle disorders ensue, including skeletal muscle hypertrophy and muscular dystrophy [32][33][34] .…”
mentioning
confidence: 99%
“…miR-489, which is highly expressed in quiescent SCs and is quickly downregulated during SC activation, helps to maintain the quiescent state of adult stem-cell populations by targeting Dek 27 . When miRNA expression in skeletal muscle is dysregulated, various skeletal muscle disorders ensue, including skeletal muscle hypertrophy and muscular dystrophy [32][33][34] .…”
mentioning
confidence: 99%
“…9 MicroRNAs (miRNAs) have been shown to have an essential role in muscle development, differentiation, and disease. [10][11][12][13][14][15] Previously, we defined a miRNA biosignature of different muscle diseases and revealed dysregulated miRNAs that were either common or unique to each muscle disease. 12 Additional studies using the dystrophic mdx mouse muscle identified dysregulated miRNAs as a result of nNOS destabilization from the muscle membrane.…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) act as negative regulators of gene expression [23][24][25][26][27][28][29] . Strikingly, a single miRNA is even able to modulate complex physiological or disease phenotypes by regulating the entire functional networks 26,30,31 .…”
mentioning
confidence: 99%